2021
DOI: 10.1186/s12884-021-04067-y
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning guided postnatal gestational age assessment using new-born screening metabolomic data in South Asia and sub-Saharan Africa

Abstract: Background Babies born early and/or small for gestational age in Low and Middle-income countries (LMICs) contribute substantially to global neonatal and infant mortality. Tracking this metric is critical at a population level for informed policy, advocacy, resources allocation and program evaluation and at an individual level for targeted care. Early prenatal ultrasound examination is not available in these settings, gestational age (GA) is estimated using new-born assessment, last menstrual pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…When the published ML model [ 19 ] was used to predict GA in the simulated data set, a similar distribution pattern of predicted GA was observed comparing the original and the simulated database from the sub-sample (Figure S1 in the Online Supplementary Document ). The simulated data set from 330 samples, with samples shipped on dry ice resulted in RMSE of 1.07 (95% confidence interval (CI) = 0.96-1.21) as compared to RMSE of 1.02 (95% CI = 0.91-1.14) for the parent data set (1318 children shipped and stored at -80°C and shipped on dry ice.)…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…When the published ML model [ 19 ] was used to predict GA in the simulated data set, a similar distribution pattern of predicted GA was observed comparing the original and the simulated database from the sub-sample (Figure S1 in the Online Supplementary Document ). The simulated data set from 330 samples, with samples shipped on dry ice resulted in RMSE of 1.07 (95% confidence interval (CI) = 0.96-1.21) as compared to RMSE of 1.02 (95% CI = 0.91-1.14) for the parent data set (1318 children shipped and stored at -80°C and shipped on dry ice.)…”
Section: Resultsmentioning
confidence: 56%
“…Baseline characteristics of the 330 children contributing the samples provided in Table 1 , were evaluated against 1318 children [ 19 ], from which this sample was sub-selected. Percentage difference for each of the metabolites, between samples shipped in dry ice and ambient temperature were calculated across all the samples ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…85.21 % (95% CI 72.31–94.65) of GAs were properly predicted to within one week. The model also showed high sensitivity (100%) and specificity (92.6%) for differentiation of preterm and term birth ( 127 ). Meenakshi et al ( 128 ) showed good results of a model to automatically estimate the GA at third trimester by using biparietal diameter and kidney length.…”
Section: Ai In the Neonatal Icumentioning
confidence: 95%